A COMPREHENSIVE STUDY OF VATA RAKTA W.S.R. TO GOUT - Rana, *Vikas; Mishra, Anjana; Mehra, B.L. (International Journal of Ayurveda and Pharma Research, 2017)
The rapid modernization in India, fast food culture, stressful and speedy life, prevalent in urban areas is spreading its wings in remote villages too. Nowadays human beings are vulnerable to many disorders due to their altered life style and food habits. Among such metabolic disorders Vatarakta is one of them.Vatarakta is more distressing and common metabolic disorder prevalent in present era. It is characterised by severe pain, tenderness, inflammation and burning sensation in the affected joints. It is a Vatapradhana tridoshaja vyadhi where Rakta is main Dushya. Vatarakta is an illness where both Vata and Rakta are afflicted by distinct aetiological factors. Sedentary lifestyle along with mental stress, consumption of non-vegetarian and highly protein diet, excessive alcohol intake are some of the precipitating factors which causes acute exacerbation of Vatarakta. The aetiological factors responsible for Gouty arthritis, pathology and clinical features are quite similar with the Vatarakta. Due to excruciating pain, inflammation, joint deformity and restricted joint movements with the risk of various complications like urate nephropathy and urate nephrolithiasis its necessary to have a complete overview on all aspects of disease for treatment. Management of Vatarakta is a challenge as it is a disease of severe morbidity, chronicity and incurable to certain extent with associated complications. With certain life style modifications like low protein diet etc. and certain Ayurveda modalities viz. Shodhana and Shamana Chikitsa its can be cure and prevented.